Science & Technology in China: A Roadmap to 2050 Strategic General Report of the Chinese Academy of Sciences - Lu, Yongxiang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This general report, sponsored by the Chinese Academy of Sciences, presents a panoramic scenario for China's modernization drive to 2050. It analyzes the evolution and laws governing the development of science and technology, describes the decisive impact of science and technology on the modernization process, predicts that the world is on the eve of an impending S&T revolution, and calls for China to be fully prepared for this new round of S&T advancement. Based on its detailed study of the demands on S&T innovation in China's modernization, it draws a framework for eight basic and strategic systems of socio-economic development with the support of science and technology, works out China's S&T roadmaps for the relevant eight basic and strategic systems in line with China's reality, further details S&T initiatives of strategic importance to China's modernization, and provides S&T decision-makers with comprehensive consultations for the development of S&T innovation consistent with China's reality. Supported by illustrations and tables of data, the general report provides researchers, government officials and even entrepreneurs with guidance concerning research directions, the planning process, and investment. It also serves as a preamble for the eighteen detailed field-specific reports of the committees assigned to craft roadmaps for each sphere of development. Founded in 1949, the Chinese Academy of Sciences is the nation's highest academic institution in the natural sciences. Its major responsibilities are to conduct research in basic and technological sciences, to undertake nationwide integrated surveys on natural resources and ecological environment, to provide the country with scientific data and consultations for government's decision-makings, to undertake government-assigned projects with regard to key S&T problems in the process of socio-economic development, to initiate personnel training, and to promote China's high-tech enterprises through its active engagement in these areas.
The World is at the Eve of a New S&T Revolution -- The New S&T Revolution Provides Historical Opportunities for China$1 (Bs Modernization -- China$1 (Bs Eight Basic and Strategic Systems for Socio-economic Development -- Twenty-two S&T Initiatives of Strategic Importance to China$1 (Bs Modernization -- S&T Innovation with Chinese Characteristics.s
Keywords: Economics; Renewable energy sources; Sustainable development; Economics/Management Science; R & D/Technology Policy; Renewable and Green Energy; Sustainable Development